Immunoprophylaxis with Dimephosphone of Some Negative Aftereffects of 2- Mercaptobenzothiazole in Animals - S.N.Farmonov; Y. Salimov (Genius Journals, 2022)
The results of studies on the toxicological assessment of the chronic effects of 2- Mercaptobenzothiazole on the organism of animals and the possibility of pharmacocorrection of the identified negative effects of this xenobiotic with T-type immunomodulators and, in particular, dimephosphone in combination with polyvinylpyrrolidone are presented.
Keywords: polyvinylpyrrolidone; toxicological; assessment; possibility